1999
DOI: 10.2118/99-09-02
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the SAGD Process In the Hangingstone Oil Sands Reservoir

Abstract: This paper presents a simulation study of a steam. assisted gravity drainage (SAGD) process applied to the Hangingstone tar sands reservoir. Two pairs of 500 m long horizontal wells installed from the surface are considered. The study was conducted to forecast recovery performance and to further understand the oil production mechanism. Results predicted that more than 60% of the oil can be produced in six years of operation with a steam-oil ratio of less than 3.0. The study was extended to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(48 citation statements)
references
References 0 publications
2
45
0
1
Order By: Relevance
“…Oil-Viscosity Gradient Uniform Oil Viscosity Ito and Suzuki 1999). Local steam-trap control is one of the effective approaches to resolve the problem related to uneven steam-chamber development along the full length of the SAGD well pair; however, this strategy is valid only in the simulation study, at least at this stage.…”
Section: J-well Sagd/jagass Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Oil-Viscosity Gradient Uniform Oil Viscosity Ito and Suzuki 1999). Local steam-trap control is one of the effective approaches to resolve the problem related to uneven steam-chamber development along the full length of the SAGD well pair; however, this strategy is valid only in the simulation study, at least at this stage.…”
Section: J-well Sagd/jagass Processmentioning
confidence: 99%
“…When the temperature of the producing fl uid becomes too hot, then production rates are reduced to lower the steam fl ow into the production well. According to Ito and Suzuki (1999), the temperature of the fl uid draining along the side of the steam chamber is approximately 30 to 40°C colder than the steam-saturation temperature. If the steam-trap temperature is set less than this temperature (e.g., 20°C), direct steam fl ow to the production well provides a match to the desired production temperature of 20°C.…”
mentioning
confidence: 99%
“…Without showing production results, they concluded feasibility of SAGD application. Ito and Suzuki (1996) observed a large amount of oil drains through steam chamber when geomechanical changes occur in the reservoir. They hence flagged the role of geomechanical change of formation during SAGD as very important.…”
Section: Sagd In Carbonate Reservoirmentioning
confidence: 99%
“…He then added that in the field due to the uneven nature of the well trajectory, it is very difficult to identify, rest alone, and control steam breakthrough. Ito and Suzuki (1996) reported an optimum temperature for a steam trap control to be between 30 to 40 o C. They referred that to fluid drainage ahead of steam chamber is 30 to 40 o C lower than steam saturation temperature. Das (2005) noticed a positive effect of sub cool temperature after exceeding 20 o C. Chen et al (2007) showed that when coupling hydraulic fracturing with steam trap control of the producer well, injectivity is dramatically improved and an effective oil production rate in the reservoir with poor vertical communication is achieved.…”
Section: Length Spacing and Placement Of Horizontal Wellsmentioning
confidence: 99%
“…Ito and Suzuki (5) studied steam-trap control with a simple two-dimensional (2D) grid system, and a drawdown into the production well of less than 40 kPa. They found that the optimum subcool values were between 30˚ C and 40˚ C. They also noted that the subcool value should be corrected for higher drawdowns which were observed at the UTF pilot.…”
Section: Steam-trap Controlmentioning
confidence: 99%